2019
DOI: 10.5194/wes-2019-53
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of the Blade Element Momentum Model on a Polar Grid and its Aeroelastic Load Impact

Abstract: Abstract. We show that the up-scaling of wind turbines from rotor diameters of 15–20 m to presently large rotors of 150–200 m has changed the requirements for the aerodynamic Blade Element Momentum (BEM) models in the aeroelastic codes. This is because the typical scales in the inflow turbulence are now comparable with the rotor diameter of the large turbines. Therefore the spectrum of the incoming turbulence relative to the rotating blade has increased energy content on 1P, 2P, ..., nP and the annular mean in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…The BEM model in HAWC2 has been compared with high‐fidelity codes many times. A comparison for the NREL 5MW in uniform inflow by Madsen et al showed very good agreement of the loading obtained by HAWC2 with results from CFD and vortex wake codes.…”
Section: Methodology For Validationmentioning
confidence: 73%
See 1 more Smart Citation
“…The BEM model in HAWC2 has been compared with high‐fidelity codes many times. A comparison for the NREL 5MW in uniform inflow by Madsen et al showed very good agreement of the loading obtained by HAWC2 with results from CFD and vortex wake codes.…”
Section: Methodology For Validationmentioning
confidence: 73%
“…The BEM model implemented in the HAWC2 aeroelastic code is used as a basis for determining the constants of Shen's tip loss correction, Equation in this article. A tip loss correction by Wilson and Lissaman is implemented in the code.…”
Section: Methodology For Validationmentioning
confidence: 99%
“…The basic BEM is modified to include wake expansion and swirl and extended with models to handle: dynamic inflow, skewed inflow, shear effect on induction, effect from large blade deflections, tip loss, and dynamic stall. The reader is referred to the recent publication of Madsen et al 44 for more details regarding the BEM implementation of HAWC2.…”
Section: Methodsmentioning
confidence: 99%
“…The turbine analyses for the presented work were performed with HAWC2 version 12.6, which is a strongly coupled aeroservo-elastic wind turbine simulation tool. The aerodynamic solver of HAWC2 (Madsen et al, 2019) uses the blade element momentum formulation (De Vries, 1979;Wilson and Lissaman, 1974) including effects of dynamic stall, dynamic inflow, wind shear on induction, tip loss, tower shadow and large blade deflections. A PID controller algorithm is used to determine the set point of the pitch bearing angle and generator torque.…”
Section: Methodsmentioning
confidence: 99%